Faktor-faktor yang Berpengaruh terhadap Praktik Seks Pranikah pada Remaja di SMA Dekat Lokalisasi di Wilayah Kabupaten Malang - Triningsih, Reni Wahyu; Widjanarko, Bagoes; Istiarti, VG Tinuk (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTThe Influence of Personal and Environmental Factors towards Premarital Sex Activities of Teenagers in High Schools Near Red-Light-Districts at Malang Regency; Increased levels of towards Premarital Sex Activities in the districts of Malang, From 404 students in Malang Regency, 116 students (29%) have had premarital sex, and 21 % of them involved in affairs without having sexual intercourse. The teenagers who live near the district were exposed to prostitution environment. The purpose of this research is to analyze the influence of personal and environmental factors towards premarital sex activities of teenagers in high schools near red-light-districts. This study used quantitative method to the design of explanatory research with cross sectional approach. Data collection using questionnaires on242 respondents (from 10th and 11th Graders) who were interviewed using structured questioner. The data analysis used univariate, bivariate technique, tested by chi-square test, and multivariate technique tested by logistic regression test. The findings of the research showed about 24 % of the teenagers have had premarital sex. variable towards teenagers’ attitudes towards premarital sex was self-esteem with the (OR= 3.695)Keywords: personal and environmental factors, premarital sex